2016
DOI: 10.1007/s11295-016-0983-1
|View full text |Cite
|
Sign up to set email alerts
|

Climate change risk management in tree improvement programs: selection and movement of genotypes

Abstract: Tree improvement programs usually consist of multiple breeding populations that target different climatic or ecological regions. Parent breeding material normally originates from and is deployed within the same breeding region, assuming optimal local adaptation of populations. Given the climate trends observed over the last several decades in western Canada, this assumption is unlikely to still be valid. This problem needs to be addressed either by delineating new deployment areas for improved planting stock o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 32 publications
(41 reference statements)
1
31
0
Order By: Relevance
“…Adaptation to cold dominates signals of local adaptation in our study of interior spruce. Strong associations among hybrid index, cold injury, and cold‐related climatic variables are congruent with patterns of adaptive variation in autumn cold hardiness for widespread conifer species (Bansal, Harrington, & St. Clair, ; Gray et al., ; Hurme, Repo, Savolainen, & Pääkkönen, ; Liepe et al., ; Rehfeldt, ), and genotype–environment associations for adaptive markers associated with cold tolerance in interior spruce and lodgepole pine (Yeaman et al., ). Adequate autumn cold hardiness development prior to potentially damaging temperatures is essential to seasonal climatic synchrony, survival, and growth.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Adaptation to cold dominates signals of local adaptation in our study of interior spruce. Strong associations among hybrid index, cold injury, and cold‐related climatic variables are congruent with patterns of adaptive variation in autumn cold hardiness for widespread conifer species (Bansal, Harrington, & St. Clair, ; Gray et al., ; Hurme, Repo, Savolainen, & Pääkkönen, ; Liepe et al., ; Rehfeldt, ), and genotype–environment associations for adaptive markers associated with cold tolerance in interior spruce and lodgepole pine (Yeaman et al., ). Adequate autumn cold hardiness development prior to potentially damaging temperatures is essential to seasonal climatic synchrony, survival, and growth.…”
Section: Discussionmentioning
confidence: 80%
“…Across AB and BC interior spruce populations, height growth in common gardens is greatest in populations from the valleys of southern BC, and decreases as tolerance to extreme cold increases with latitude. Growth also decreases locally as tolerance of deep snow pack and short growing seasons increases with elevation (De La Torre, Jaquish, et al., ; Gray et al., ; Liepe, Hamann, Smets, Fitzpatrick, & Aitken, ; Rehfeldt, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although this study was not designed to study local optimality or to be used to derive practical assisted migration guidelines, provenances that originated near the vicinity of the study site showed the best combination of long-term performance in growth and survival in the field. Local provenances (central Alberta) originated slightly southeast of the study site which corresponds to a short northwest transfer as was recommended by Gray et al, 2016 to account for climate change that has already occurred over the last several decades. The provenances that showed both poor growth and low survival came from the Alberta Foothills (lower-left quadrant in Figure 2…”
Section: Local Adaptation and Trade-offsmentioning
confidence: 99%
“…Previous work on white spruce provenances in different parts of its distribution suggests that transfers toward the north can increase growth rates (e.g., Gray et al., ; Lesser & Parker, ; Li, Beaulieu, & Bousquet, ; Lu et al., ; Rweyongeza, Yang, Dhir, Barnhardt, & Hansen, ). A recent study proposed relatively short northward transfers for Alberta, with growth and survival of transferred seed sources putatively limited by cold temperatures in the north of the province (Gray et al., ). All these studies analyzed the response of tree growth to different planting environments, but there is little understanding of the physiological causes of different local adaptations.…”
Section: Introductionmentioning
confidence: 99%
“…For long‐lived species such as trees, future climate models are being used to guide translocation decisions with the aim to develop resilient plantings better adapted to future climates (Harrison et al ). Assisted gene flow (the movement of germplasm within the species' natural distribution) and assisted migration (the movement of germplasm within or outside their natural distribution) are thus being increasingly integrated into conservation strategies (Aitken & Whitlock ; Gray et al ). In a restoration context, this involves strategies, such as climate‐adjusted provenancing, which aim at enriching local plantings with seed predicted to be genetically adapted to future climates of the planting site (Prober et al ).…”
Section: Introductionmentioning
confidence: 99%